Application of enzymes in feedstock preparation for the production of spray dried soursop (Annona muricata L.) powder - Chang, L. S.; Karim, Roselina; Mohammed, Abdulkarim Sabo; Mohd Ghazali, Hasanah (Faculty of Engineering, Universiti Putra Malaysia, 2016)
Soursop is a local fruit that is susceptible to spoilage. In this study, spray drying was used to preserve the fruit as a dry powder. Prior to drying, commercially available enzyme preparations, Pectinex® Ultra SP-L, Fungamyl® 800 L and Celluclast® 1.5 L (Novozymes, Denmark), were used in a pre-treatment step to macerate and liquefy soursop mesocarp. Results showed that there was a synergetic effect when the pectolytic enzyme was applied together with the cellulolytic enzyme where the liquefied puree was obtained within shorter incubation time and was smooth with low viscosity, making the puree suitable as feedstock for spray drying. RSM study on the effect of Celluclast® 1.5 L concentration (0 to 2 % v/w) at fixed Pectinex® Ultra SP-L concentration (1.5 % v/w), maltodextrin level (20 to 40 % w/w), and spray drying inlet temperature (130 to 160 °C) gave a polynomial model that was significantly (p ≤ 0.05) fitted for process yield, moisture content, water activity, hygroscopicity, and stickiness. Multiple optimization of the process indicated Celluclast® 1.5 L concentration of 1.29 % (v/w) with maltodextrin of 37.42 % (w/w) that spray dried at inlet temperature of 156 °C was able to produce soursop powder that had optimal properties.